International multicenter study comparing demographics, therapy and outcomes in bleeding from Mallory Weiss tears and peptic ulcers - Tham, Jennifer E.; Lynch, Lucy; Laursen, Stig B.; Laine, Loren; Dalton, Harry R.; Ngu, Jeffrey; Redondo-Cerezo, Eduardo; Schultz, Michael; Murray, Iain; Michell, Nick; Morris, Alan J.; Nielsen, Michael M.; Stanley, Adrian J. (Endoscopy International Open, 2022)
Background and study aims Mallory Weiss tears (MWTs) are relatively uncommon causes of upper gastrointestinal bleeding (UGIB), and patients are generally considered at low risk of poor outcome, although data are limited. There is uncertainty about use of endoscopic therapy. We aimed to describe and compare an international cohort of patients presenting with UGIB secondary to MWT and peptic ulcer bleeding (PUB).Patients and methods From an international dataset of patients undergoing endoscopy for acute UGIB at seven hospitals, we assessed patients with MWT bleeding, including the endoscopic stigmata and endoscopic therapy applied. We compared baseline parameters, rebleeding rate, and 30-day mortality between patients with MWT and PUB.Results A total of 3648 patients presented with UGIB, 125 of whom (3.4 %) had bleeding from a MWT. Those patients were younger (61 vs 69 years, P < 0.0001) and more likely to be men (66 % vs 53 %, P = 0.006) compared to the patients PUB. The most common endoscopic stigmata seen in MWTs were oozing blood (26 %) or clean base (26 %). Of the patients with MWT, 53 (42 %) received endoscopic therapy. Forty-eight of them (90 %) had epinephrine injections and 25 (48 %) had through-the-scope clips. The rebleeding rate was lower in MWT patients compared with PUB patients (4.9 % vs 12 %, P = 0.016), but mortality was similar (5.7 vs 7.0 %, P = 0.71).Conclusions Although patients presenting with MWT were younger, with a lower rebleeding rate, their mortality was similar to that of patients with PUB. Endoscopic therapy was applied to 42 % MWT patients, with epinephrine injection as the most common modality.